Role of Nitya Virechan and Pathya in Cirrhotic Ascites (AYUSHDHARA, 2023)
Cirrhosis of liver is an imperceptible disease due to any of the various long standing liver diseases which gradually leads to scarring of the liver tissues. This scarring or fibrosis is the consequence from the healing of the injured liver cells. Cirrhosis is the most common cause of ascites and accounts for almost 85% of all cases. [1] Cirrhotic ascites thus accounts as one of the major complications of Liver cirrhosis. Ayurvedic medicines give a promising result in the management of such decompensated liver disease. We hereby report a successfully managed case of a 53 year old male patient suffering from Cirrhotic Ascites. Post complication with hepatorenal syndrome and hepatogenous diabetes the patient was advised for liver and kidney transplant, as also his ascitic tapping was done multiple times; however he approached for alternative therapy in form of Ayurvedic medicine and was healed. Ascites can be correlated to Jalodar in Ayurvedic concept so the treatment protocol included the exclusive Ayurvedic treatment of Nitya virechan i.e., constant purgation mentioned as the principle treatment for Jalodar along with other supportive medications for liver malfunctioning. Therapeutic diet played an important role for the treatment. During and after treatment no adverse effects were found moreover patient was at comfort with the treatment and the distension of abdomen was negligible, patient also stopped taking insulin, while swelling was reduced remarkably.